Insights into additional lactone-based signaling circuits in Streptomyces: existence of acyl-homoserine lactones and LuxI/LuxR homologs in six Streptomyces species - Salehi-Najafabadi, Amir; Tehrani Fateh, Sepand; Amoabediny, Ghasem; Hamedi, Javad (Frontiers in Microbiology, 2024)
Acyl-homoserine lactones (AHLs), mediating pivotal physiological activities through Quorum Sensing (QS), have conventionally been considered limited to Gram-negative bacteria. However, few reports on the existence of AHLs in Gram-positive bacteria have questioned this conception. Streptomyces, as Gram-positive bacteria already utilizing a lactone-based QS molecule (i.e., Gamma-Butyrolactones), are yet to be explored for producing AHLs, considering their metabolic capacity and physiological distinction. In this regard, our study examined the potential production of AHLs within Streptomyces by deploying HPLC-MS/MS methods, which resulted in the discovery of multiple AHLs production by S. griseus, S. lavendulae FRI-5, S. clavuligerus, S. nodosus, S. lividans, and S. coelicolor A3(2). Each of these Streptomyces species possesses a combination of AHLs of different size ranges, possibly due to their distinct properties and regulatory roles. In light of additional lactone molecules, we further confirm that AHL-and GBLsynthases (i.e., LuxI and AfsA enzyme families, respectively) and their receptors (i.e., LuxR and ArpA) are evolutionarily distinct. To this end, we searched for the components of the AHL signaling circuit, i.e., AHL synthases and receptors, in the Streptomyces genus and we have identified multiple potential LuxI and LuxR homologs in all 2336 Streptomyces species included in this study. The six Streptomyces of interest in this study also had at least four LuxI homologs and 97 LuxR homologs. As a conclusion, AHLs, and associated gene regulatory systems could be more widespread within the prokaryotic realm than previously believed, potentially contributing to the control of secondary metabolites (e.g., antibiotics) and their complex life cycle, which leads to substantial industrial and clinical applications.